Factors Associated With Readmission in the United States Following Hospitalization With Coronavirus Disease 2019. (20th May 2021) - Verna, Elizabeth C; Landis, Charles; Brown, Robert S; Mospan, Andrea R; Crawford, Julie M; Hildebrand, Janet S; Morris, Heather L; Munoz, Breda; Fried, Michael W; Reddy, K Rajender
Abstract: Background: Patients hospitalized for coronavirus disease 2019 (COVID-19) may experience complications following hospitalization and require readmission. In this analysis, we estimated the rate and risk factors associated with COVID-19–related readmission and inpatient mortality. Methods: In this retrospective cohort study, we used deidentified chargemaster data from 297 hospitals across 40 US states on patients hospitalized with COVID-19 from 15 February 2020 through 9 June 2020. Demographics, comorbidities, acute conditions, and clinical characteristics of first hospitalization are summarized. Multivariable logistic regression was used to measure risk factor associations with 30-day readmission and in-hospital mortality. Results: Among 29 659 patients, 1070 (3.6%) were readmitted. Readmitted patients were more likely to have diabetes, hypertension, cardiovascular disease (CVD), or chronic kidney disease (CKD) vs those not readmitted ( P  < .0001) and to present on first admission with acute kidney injury (15.6% vs 9.2%), congestive heart failure (6.4% vs 2.4%), or cardiomyopathy (2.1% vs 0.8%) ( P  < .0001). Higher odds of readmission were observed in patients aged >60 vs 18–40 years (odds ratio [OR], 1.92; 95% confidence interval [CI], 1.48–2.50) and those admitted in the Northeast vs West (OR, 1.43; 95% CI, 1.14–1.79) or South (OR, 1.28; 95% CI, 1.11–1.49). Comorbidities including diabetes (OR, 1.34; 95% CI, 1.12–1.60), CVD (OR, 1.46; 95% CI, 1.23–1.72), CKD stage 1–5 (OR, 1.51; 95% CI, 1.25–1.81), and CKD stage 5 (OR, 2.27; 95% CI, 1.81–2.86) were associated with higher odds of readmission; 12.3% of readmitted patients died during second hospitalization. Conclusions: Among this large US population of patients hospitalized with COVID-19, readmission was associated with certain comorbidities and acute conditions during first hospitalization. These findings may inform strategies to mitigate risks of readmission due to COVID-19 complications. Abstract : In this retrospective cohort study, we assessed the rate and risk factors associated with coronavirus disease 2019–related readmission and inpatient mortality in the United States.